Artemisinin Derivatives Target Topoisomerase 1 and Cause DNA Damage in Silico and in Vitro - Kadioglu, Onat; Chan, Ariel; Cong Ling Qiu, Alena; Wong, Vincent Kam Wai; Colligs, Vanessa; Wecklein, Sabine; Freund-Henni Rached, Halima; Efferth, Thomas; Hsiao, Wen-Luan Wendy (Frontiers in Pharmacology, 2017)
DNA topoisomerases 1 and 2 are enzymes that maintain DNA topology and play important essential genome functions, including DNA replication and transcription. Aberrant topoisomerases cause genome instability and a wide range of diseases, cancer in particular. Both Topo 1 and 2 are the targets of valuable anticancer drugs, such as camptothecin. It has been previously shown that artemisinin, a sesquiterpene lactone from Artemisia annua L. also known as qinghaosu, possesses anti-cancer effects and one of its derivatives, artesunate inhibits Topo 2. In this study, we evaluated artemisinin and 40 derivatives as potential Topo 1 inhibitors at first by in silico molecular docking analyses. Five compounds that showed comparable binding energies and similar docking poses were selected for in vitro cytotoxicity test and Comet assay for DNA damage. WWLL-013, WWLL-022 and WWLL-1098 showed the lowest binding energy also induced DNA damage in the Comet assay. CMK-0298 and CMK-0398 intercalated into DNA and induced mild DNA damage. All selected compounds, WWLL-013 in particular, were more cytotoxic towards the rat tumor cells than to the normal cells. In conclusion, the artemisinin derivatives such as CMK-0298, CMK-0398, WWLL-013, WWLL-022 and WWLL-1098 can be further developed as Topo 1 inhibitors.